Stock structuring in Asian green mussel Perna viridis population along the Indian coast based on shell morphometrics and RAPD markers - P R, Divya; Thomas, P C; Gopalakrishnan, A; Sathianandan, T V; Paulton, M P (The Indian Journal of Animal Sciences, 2012)
In this study, shell morphometrics and random amplified polymorphic DNA (RAPD) techniques were used to evaluate the genetic variability in 4 wild populations of Perna viridis (Hâ‰ˆ2500 km apart) along the Indian coast. The phenotypic stocks of mussels were separated using canonical discriminant function analysis. Scatter plots developed with CDA depicted overlapping clusters, indicative of the morphological uniformity of the species along the Indian coast, while Andaman population was forming a separate cluster. RAPD profiles generated from green mussels using 6 primers amplified a total of 43 different fragments ranging from <300 bp to 2500 bp, of which 30 were polymorphic. High genetic variability and moderate genetic differentiation (0.126) was noted among the populations. Percentage of polymorphism among green mussels ranged from 30.2% (Dona Paula) to 79.1% (Andamans). The observed genetic homogeneity among the green mussels of Indian coast indicated their high level of genetic mixing and it may be attributed to the pelagic larval dispersal along with coastal currents.